Studying the Effect of Partially Purified ArthrobacterB1.Polysaccharide on Nucleosomal Distribution of HepG2 Tumor Cell Line - Al-Saffar, Ali Z; Al-Roubaie, Nawar B; Al-Shaibani, Abdul Wahid B (Al-Nahrain Journal of Science, 2018)
This study was designed to investigate the effect of partially purified polysaccharide extracted from ArthrobacterB1 on the DNA banding pattern of HepG2 tumor cell line invitro. The polysaccharide was extracted from Arthrobacter B1using phenol sulfuric acid methodwith a recovery yield of 181mg. Partial purification of polysaccharide was performed by using sepharose Cl-6B gel filtration chromatography and two peaks were obtained. Chemical analysis involving the estimation of carbohydrate and protein contents which showed that the large first peak contained the higher carbohydrate contents (30.1%) as compared with the crude polysaccharide 15.9% with low protein constituents (5.7%).The effect of Arthrobacter B1polysaccharide on HepG2 tumor cells was examined by studying whether bacterial polysaccharide participating in affecting the structure of tumor cell’s DNA or not. Results indicated that only intact nucleosomal DNA bands were separated on the gel for the untreated cells as compared with the banding pattern of the colchicine treated DNA, in which besides to intact nucleosomal DNA, mononucleosomes, dinucleosomes and oligonucleosomes were separated on the gel following electrophoresis process. Such pattern does not affected by the gradual increase in MNase concentration. On the other hand, the DNA banding pattern for the cells treated with Arthrobacter B1 polysaccharide showed significant effect by the separation of nucleosomal DNA, in which mononucleosomes, dinucleosomes and oligonucleosomes were clearly separated from intact nucleosomal DNA, and such effect was markedly appeared by increasing the concentration of MNase as compared with the cells treated colchicine.